Dissolution, diffusion, and penetration of H in the group VB metals investigated by first-principles method. (8th November 2019) - Qin, Jiayao; Wang, Zhongmin; Wang, Dianhui; Wu, Yang; Zhong, Yan; Hu, Chaohao; Zhou, Huaiying
Abstract: The group VB metals (V, Nb, Ta) are referred to as one of the most valuable hydrogen separation membrane materials because of their advantages over Pd. To evaluate the hydrogen-permeation performance of the three metals, their structure stability, H-solubility, H-diffusivity, H-permeability, and elastic stiffness tensors have been investigated using the first-principles method. Our results reveal that the tetrahedral interstitial site (TIS) is favorable position for H-occupying, but mainly because H-solution enthalpy is the lowest. H-diffusion coefficient follows the order of V > Nb > Ta, H-permeability and H-permeation flux follow the order of Nb > V > Ta. The attractive interactions between H atoms are weak, so it is impossible to form H2 molecules inside the metals, and all metal hydride phases present good ductility. The calculated Debye temperature is basically consistent with the experimental value. These results provide fundamental data for the further design of alloy membranes based on VB metals. Highlights: H-permeation in VB metals (V, Nb, Ta) was systematically studied and compared. Zero point energy was considered to ensure the accuracy of the calculations. The preferred adsorption site and diffusion path of H atom was determined. The calculated results agreed well with literature data.